Kajian Psikoanalisis Tokoh Mat Kontan Dalam Naskah Malam Jahanam Karya Motinggo Boesje - Winiarti, Winiarti; Firdaus, Sifa Yuha; Nugroho, Rudi Adi (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2024)
This study aims to reveal the psychological condition of the main character, Mat Kontan, in the script of the drama Malam Jahanam by Motinggo Boesje. The literary approach used is based on Sigmund Freud's psychoanalytic theory, which examines the structure of personality and defense mechanisms. This study employs a qualitative, descriptive-analytical method. The researcher gathered data in the form of excerpts from the dialogue in the Malam Jahanam drama script, then presented the psychological condition of the character Mat Kontan in the form of a narrative description. Based on the analysis, it was found that Mat Kontan has an unstable psychological condition in the aspects of id, ego, and superego. The id aspect of Mat Kontan is evident in his tendency to excessively boast about his children, wife, and favorite bird. Mat Kontan has an exaggerated inclination in the id aspect towards his bird, leading to an inability to control his ego and superego. The ego aspect of Mat Kontan is apparent when he cannot control himself, spending the money from his fishing haul to buy a turtledove. Mat Kontan's superego is demonstrated when he intends to kill the person responsible for the death of his beloved bird. In terms of defense mechanisms, Mat Kontan exhibits rationalization and reaction formation. He uses rationalization with Paijah to make his pleasure in birds acceptable. Mat Kontan employs reaction formation as an ego defense mechanism to kill Soleman because he has caused anxiety regarding his id.